China's agricultural development: challenges and prospects - Dong, Xiao-Yuan; Song, Shunfeng; Zhang, Xiaobo (Ashgate, 2006)
Introduction: China's agricultural development: challenges and prospects, Xiao-Yuan Dong, Shunfeng Song and Xiaobo Zhang. Overview of the Challenges and Options: High performing Asian economies: retrospect and prospect, Robert W. Fogel; Several strategic and political thoughts on boosting rural development, Justin Yifu Lin; Conflicts and problems facing China's current rural reform and development, Xiwen Chen; China's rural economy and the path to a modern industrial state, Scott Rozelle and Jikun Huang; Rural development strategy in Western China under WTO, Shenggen Fan; Taiwan's agricultural development: experience and lessons, Chia-Chu Hou and Jack W. Hou. The performance and potentials of China's agriculture: production and productivity growth in Chinese Agriculture: new nation and regional measures, Shenggen Fan and Xiaobo Zhang; County-level agricultural production efficiency in China: A spatial analysis, Zhuo Chen and Wallace E. Huffman; Impact of land fragmentation on rice producers' technical efficiency in Southeast China, Shuhao Tan, Nico Heerink, Arie Kuyvenhoven and Futian Qu; Future prospects of grain supply and demand in China: a regionalized multi-market model simulation, Wencong Lu; How well will China handle its demand for grain when it peaks, Guanzhong James Wen. Agricultural Risk Management: Agricultural income risk and acreage decision in China: analysis of the alternative relationship between soybeans and corn, Qingsen Mao; Reforms, risks and commercial-cereal crop diversification: evidence from Chinese provinces, Weiyong Yang; An empirical analysis on farmer's demand of alternative types of insurance in China, Holly H. Wang and Guangwen He; Price behavior in China's wheat futures market, Wen Du and Holly H. Wang; Index.